An Open Dialogue-informed approach to mental health service delivery: experiences of service users and support networks. (4th July 2021) - Twamley, Iseult; Dempsey, Maria; Keane, Nicola
Abstract: Background: Open Dialogue (OD) is a needs-based, service-user initiated approach to mental health service delivery that emphasises dialogue, and shared understanding between service users, and their support network. Aims: The aim of this study was to explore the lived experience of being part of an OD-informed mental health service in Ireland. Method: Data were collected through semi-structured group interviews and analysed using thematic analysis. Results: Three primary themes were identified across the data set namely: diversity across practice; unpacking the taken-for-granted and mental health as shared experiences. Participants experienced enhanced communication, improved relationships with mental health staff and developed shared understandings of mental health. Conclusions: This small-scale implementation demonstrates the received value for service users and their networks of an OD-informed approach within a traditional care pathway. As a relational and collaborative way of working, it requires a shift in clinical practice for mental health staff and service users that is experienced as a welcome change from treatment-as-usual (TAU).